2020
DOI: 10.5144/0256-4947.2020.281
|View full text |Cite
|
Sign up to set email alerts
|

Door-to-balloon time in the treatment of ST segment elevation myocardial infarction in a tertiary care center in Saudi Arabia

Abstract: BACKGROUND: Atherosclerotic heart disease is still a leading cause of mortality despite improvements in cardiovascular care. Percutaneous coronary intervention (PCI) is the recommended reperfusion therapy in acute ST-elevation myocardial infarction (STEMI), and the international guideline is to achieve a door-to-balloon (D2B) time within 90 minutes of patient arrival to an emergency department (ED). OBJECTIVES: Describe interventions, data for the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Several studies have also found that the D2D time in transfer from other hospital groups is shorter than the directed to PCI centre group ( 37 , 38 ). Communication between the referring hospital and the PCI centre can activate the catheterization team and reduce the DTD time, allowing patients transferred from other hospital groups to receive early revascularization therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also found that the D2D time in transfer from other hospital groups is shorter than the directed to PCI centre group ( 37 , 38 ). Communication between the referring hospital and the PCI centre can activate the catheterization team and reduce the DTD time, allowing patients transferred from other hospital groups to receive early revascularization therapy.…”
Section: Discussionmentioning
confidence: 99%
“…One of the factors that decreased mortality of STEMI patients is early PCI that suggested that door to balloon time <90 min. [ 38 39 40 ] Our study considered time interval between arrival at PCI hospital and reperfusion therapy. We found longer mean of this time in our patients who died.…”
Section: Discussionmentioning
confidence: 99%
“…According to the American heart association (AHA) and the American college of cardiology (ACC) guidelines, the door to balloon time should be within 90 minutes for STEMI patients. 28 Less than 50% of patients with STEMI underwent thrombolysis or PCI in the previously reported Indian ACS registries. 29 The treatment and outcomes of ACS were assessed in a large prospective CREATE registry study in India.…”
Section: Discussionmentioning
confidence: 99%